Patient experiences of an intensive care Liaison Nurse support service. (August 2022) - Sjöstedt, Viktoria; Bladh, Anna; Chaboyer, Wendy; Johansson, Lotta
Abstract: Objectives: To illuminate patients' experiences of being a part of an liaison nurse support service focused on supporting recently transferred intensive care unit patients. Research methodology/design: A qualitative inductive descriptive design including in-depth interviews was chosen. Setting: A project including an liaison nurse support service-intervention was undertaken during a 16-week period at a University hospital in Sweden. The liaison nurse support service was available Monday–Friday 10 am – 6 pm and nurses visited the patient 1–4 times after transfer to the ward. Main outcome measures: Of the 109 patients who were visited by the liaison nurse support service, 14 agreed to be interviewed about their experiences of the transfer. Data was analysed by inductive content analysis. Findings: One overall theme, An advocate in a vulnerable situation emerged from the data. Four subthemes were identified: Ensures transfer of information between the intensive care unit and the general ward, Makes the circumstances understandable and coordinates between the care levels and Offers emotional support and stability in an uncertain situation. Conclusion: The liaison nurse support service contributed to ensuring accurate transfer of information, solved problems when the patient themselves did not have control or strength and provided emotional support.